2000
DOI: 10.1152/jappl.2000.88.4.1277
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue lipolysis is increased during a repeated bout of aerobic exercise

Abstract: The goal of the study was to examine whether lipid mobilization from adipose tissue undergoes changes during repeated bouts of prolonged aerobic exercise. Microdialysis of the subcutaneous adipose tissue was used for the assessment of lipolysis; glycerol concentration was measured in the dialysate leaving the adipose tissue. Seven male subjects performed two repeated bouts of 60-min exercise at 50% of their maximal aerobic power, separated by a 60-min recovery period. The exercise-induced increases in extracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
1
10

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 36 publications
2
70
1
10
Order By: Relevance
“…97 GH is known to be secreted during the type of exercise for which ANP action was proposed. 95,98 However, GH is a less potent lipolytic agent than catecholamines or ANP; moreover, the timecourse of appearance of the lipid mobilizing effect of GH appears at least 2 hours after intravenous injection of GH. 99 Thus, involvement of GH-related lipolytic effects, if any, cannot account for the acute and short-term lipid mobilization promoted by exercise.…”
Section: Lafontan Et Al Metabolic Role For Atrial Natriuretic Peptidementioning
confidence: 99%
“…97 GH is known to be secreted during the type of exercise for which ANP action was proposed. 95,98 However, GH is a less potent lipolytic agent than catecholamines or ANP; moreover, the timecourse of appearance of the lipid mobilizing effect of GH appears at least 2 hours after intravenous injection of GH. 99 Thus, involvement of GH-related lipolytic effects, if any, cannot account for the acute and short-term lipid mobilization promoted by exercise.…”
Section: Lafontan Et Al Metabolic Role For Atrial Natriuretic Peptidementioning
confidence: 99%
“…VO 2max ) does not affect leptin levels in healthy subjects (8,9), but long-term exercise (2 h) leads to a reduction in leptin levels (10,11). It is well established that growth hormone (GH) secretion increases during exercise (12) and depends on exercise intensity (13 -16), duration (17,18), age and training status (19). Whether ghrelin is the main physiologic secretory stimulus of GH is debated: recent evidence suggests that ghrelin is not involved in the exercise-induced stimulation of GH secretion during a submaximal aerobic exercise (20), whereas it has been suggested that the preprandial increase in ghrelin levels drives the GH surge postprandially (21).…”
Section: Introductionmentioning
confidence: 99%
“…White adipose tissue energy needs are relatively small, and most of the substrates taken up by WAT are used to build-up its lipid droplet [26], and ATP needs are largely devoted to this task. Adrenergic stimulation such as that of exercise stimulates both lipolysis and glycolysis (the latter mainly from glycogen stores) [27,28], freeing lactate and protons to the bloodstream [9,24]. Local acidity increases the dissociation of oxyhemoglobin, freeing more oxygen in a tissue which has little need for it (low ATP needs, suffi cient glycolytic-derived ATP, few mitochondria).…”
Section: Blood Flow and Oxygen Supplymentioning
confidence: 99%